Inclusive Education : Towards Social Justice, Achievement of Equality and Advancement of Human Rights - Maguvhe, Mbulaheni O., (Educational Research E-Books Online, Collection 2025., 2025)
The book is advocating for new inclusive curriculum and assessment initiatives. New inclusive education initiatives will encourage inclusive education practitioners from Early Childhood Development to post-school to focus on the inclusion of the full range of diverse learning needs. A key responsibility of different role-players in curricula and assessment is to provide curricula, assessment and instructional support to public adult learning centres, full-service schools, resource centres and further education institutions in the form of comprehensive learning programmes, learning support materials and assessment instructions. The book will equip every reader with skills, knowledge and experience to review and improve curricula and assessment in order to expand learners' participation in different education settings.